Design and Development of an Android-Based POS Application for MSME Sales Optimization - Bagus Karandika (Journal of Digital Business and Data Science, 2026)
Backround: The rapid growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia has created an urgent demand for affordable yet robust digital management tools. Conventional cash register systems frequently fail to deliver real-time inventory control, structured sales reporting, or multi-role access management constraints that impede operational efficiency and business scalability. Objective: This study aims to design and develop a hybrid Android-based Point of Sale (POS) application, designated GS Baby Care POS, specifically engineered to address those operational gaps in the MSME retail sector.Method: The application was built using an agile development methodology combining Vue.js 3, Capacitor JS, and a Supabase (PostgreSQL) cloud backend, delivering a JAMStack-plus-Mobile-Hybrid architecture. Findings and Implications: System evaluation employed Black-Box Functional Testing and the System Usability Scale (SUS) questionnaire administered to fifteen respondents. Functional testing confirmed that all core modules including role-based authentication, variant-level inventory management, shift tracking, customer relationship management, and financial dashboards — operated without defect. SUS assessment yielded a mean score of 83.7 (Grade B, Excellent), indicating high user acceptance. The application demonstrably reduced average transaction processing time by 42 percent and provided real-time business analytics previously unavailable to the target enterprise.Conclusion: These results confirm that a cloud-native, hybrid-mobile POS system constitutes a viable and cost-effective solution for MSME digital transformation.